ANALISIS PROSES PENGECATAN EXCAVATOR NGH 320 MENGGUNAKAN KONSEP SIX SIGMA DI PT CATERPILLAR INDONESIA - Benny Osta Nababan; Budi Setiawan (Economicus : Jurnal Ekonomi dan Manajemen, 2021)
This study aims to identify the causes of low quality and provide suggestions for improving the painting process of the NGH 320 Excavator. The method used to conduct this research is the Six Sigma DMAIC method. With a sigma level value of 3.86, the painting process for the Excavator NGH 320 still requires process improvements to increase the sigma value. Based on the Pareto Diagram, the types of defects that dominate in the painting process are Runs/Saging (too much paint attached) of 65.08% and Fish Eyes (painting defects in the form of craters on the top coat paint) of 14.29%. At the repair stage using steps 5W + 1H and FMEA, the results obtained are 6 recommendations for improvement, namely providing IQA (Incoming Quality Assurance) in the goods receiving area, changing the operator's rolling schedule to every 1 or 2 weeks, changing the size of the spray gun nozzle to a larger size. small size (size 413 to 411), installing a filter regulator on the mixing machine, conducting training on understanding the working methods used, providing new tools for cleaning plates and some suggestions from the results of this research on the painting process of the NGH 320 Excavator.